Optimizing microgrid designs towards net-zero emissions for smart cities: addressing energy disparities and access issues in Northern and North-eastern India - Arunkumar, Albert Paul; Kuppusamy, Selvakumar (Institute of Advanced Engineering and Science, 2025)
Providing affordable and clean energy is a significant sub-sector of the Smart Cities Mission proposed by India. This research investigates the development of optimal microgrid designs for smart cities in northern and north-eastern India to address regional energy disparities and access issues. In the northern zone, characterized by uneven urban-rural infrastructure and high-power demand, microgrids offer localized, reliable solutions that reduce dependency on centralized systems and enhance energy efficiency. In the north-eastern zone, where geographical isolation and underdeveloped infrastructure hinder energy access, microgrids provide decentralized power generation and distribution, improving access in remote areas. The proposed microgrid designs aim to enhance energy reliability, efficiency, and accessibility by integrating renewable energy sources. The proposed system is analyzed for technical and economic feasibility based on critical factors such as cost of energy (COE), loss of power supply probability (LPSP), and the renewable fraction (RF). The renowned particle swarm optimization (PSO) algorithm is used to optimize the system size to achieve better performance in terms of technical and economic aspects. A proper energy management technique ensures the energy balance between the demand side and the distributed energy sources. A typical 24-hour household load profile is used for the optimization.